Sorani Kurdish and Minimalism - Gharib, Hiba Esmail (Journal of University of Human Development, 2016)
Sorani is a dialect of Kurdish that is spoken in many countries of the world. In Sorani there is an agreement marker that appears on the verb and makes the verb agrees with the subject in person and number. A close examination of the nature of the agreement marker in Sorani shows that it is not obvious whether it is a suffix or a clitic. In this research I will discuss the properties of the affixes and clitics in general, and then apply them to the data in Sorani to decide whether the agreement marker is an affix or a clitic. The agreement marker in Sorani in the past tense verbs requires reconsideration as in the past tense; the agreement marker appears on the object instead of the verb. Subject agreement in Sorani is considered a challenge to the syntactic theories as there is no good explanation available to understand this phenomenon. In my research will explore the nature of this agreement marker as this would be the key to explaining the agreement phenomenon in Sorani.